The Role Of Green Marketing And Brand Image In Shaping The Decision To Stay At Ecolodge Bukit Lawang Resort - Yudha Maulana Putra; Lubis, Adelina; Ikbar Pratama (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
This study aims to examine the role of green marketing and brand image in shaping the decision to stay at Ecolodge Bukit Lawang Resort. Ecolodge Bukit Lawang Resort, located in the Bukit Lawang area, North Sumatra, offers an eco-friendly tourism concept that focuses on sustainability and nature conservation. Therefore, understanding how green marketing practices and brand image can influence consumer behavior in making decisions to stay is important. This study uses a quantitative approach with a survey of 100 visitors who have stayed at Ecolodge. Data were analyzed using multiple regression methods to test the influence of green marketing (eco-friendly products, green promotions, and sustainability policies) and brand image (trust, associations, and perceived quality) on consumer decisions. The results showed that both factors had a significant influence on the decision to stay. Green marketing plays an important role in creating a positive image that influences consumer trust, while a strong brand image strengthens the decision to stay. These findings provide insight for Ecolodge Bukit Lawang Resort managers to focus more on developing green marketing strategies and strengthening brand image in order to increase the resort's appeal as an ecologically responsible tourist destination.